Novel polycarboxylic acid grafted copolymer material and preparation method thereof

By forming a dense self-assembled nanocarbonized film in the polycarboxylic acid graft copolymer, the problem of reduced anti-corrosion performance of existing materials in high salt spray, high temperature and high hardness water environments is solved, and the mechanical strength of the material is significantly improved. and durability, suitable for a variety of harsh industrial environments.

CN119350634APending Publication Date: 2025-01-24宋佳瑞
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411554035.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-03
Publication Date
2025-01-24

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of protective agents, and discloses a novel polycarboxylic acid grafted copolymer material and a preparation method thereof.The material is prepared from, by mass, 20-30% of polyacrylic acid with the molecular weight ranging from 4000 to 7000, 20-30% of polycarboxylate with the molecular weight ranging from 20% to 30% of acrylic acid with the molecular weight ranging from 20% to 30% of acrylic acid with the molecular weight ranging from 20% to 30% of acrylic acid with the molecular weight ranging from 20% to 30% of acrylic acid The molecular weight of the polymaleic acid is 2000 to 4500, and the polymaleic acid accounts for 10 to 20 percent; the purity of the octadecyl propanolamine is 97 to 99 percent, and the octadecyl propanolamine accounts for 15 to 25 percent; the surfactant is selected from tallow amine, hexadecylamine and octadecylamine and accounts for 5-15%, and the content of amino groups in the surfactant is 25-35%; and a bifunctional catalyst, which accounts for 0.8 to 1.2%. According to the novel polycarboxylic acid grafted copolymer material disclosed by the invention, a compact self-assembled nano carbonized film is formed, so that the anti-corrosion capability of a coating is remarkably enhanced. In a high salt mist and corrosive environment, the material shows extremely high durability, and can effectively protect a metal substrate from corrosion, prolong the service life of equipment and reduce maintenance requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of protective agents, in particular to a new polycarboxylic acid graft copolymer material and a preparation method thereof. Background Art

[0002] Polycarboxylic acid graft copolymers are a class of important functional materials widely used in the fields of corrosion protection, anti-scaling and water treatment. They are endowed with unique chemical and physical properties by grafting different functional groups on the polymer backbone. These materials are often used in industrial circulating water systems, petrochemical equipment and other application scenarios with high protection requirements, which can significantly increase the service life of equipment and reduce maintenance costs.

[0003] Existing polycarboxylic acid graft copolymers are usually grafted with other functional monomers, such as alkylamine or phosphoric acid groups, on the main chain of polyacrylic acid or polymaleic acid to enhance their anti-corrosion and anti-scaling performance. These polymers can effectively prevent the adhesion of corrosive ions and sediments in water by forming a protective film, thereby protecting the metal surface and maintaining the efficient operation of the equipment. At the same time, these materials also have good biocompatibility and environmental protection properties, and are widely used in water treatment and environmental protection fields.

[0004] Although existing polycarboxylic acid graft copolymers have good biocompatibility and environmental protection properties, they still have some shortcomings. In high salt spray and high temperature environments, the corrosion resistance of the coating is easily reduced, and the coating may crack and peel off after long-term exposure. In addition, the anti-scaling performance of some materials in high-hardness water environments is not ideal, and the formation of scale cannot be completely avoided, resulting in reduced equipment efficiency and increased energy consumption. At the same time, under extreme temperature conditions, the mechanical strength and durability of these materials also have certain limitations, limiting their application in more harsh industrial environments. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a new polycarboxylic acid graft copolymer material and a preparation method thereof. The new polycarboxylic acid graft copolymer material of the present invention forms a dense self-assembled nanocarbonized film, exhibits excellent anti-corrosion and anti-scaling properties in high salt spray, high temperature and high hardness water environments, significantly improves the mechanical strength and durability of the material, adapts to a variety of harsh industrial environments, effectively prolongs the life of equipment, and reduces maintenance costs.

[0006] To achieve the above objectives, the present invention is implemented by the following technical scheme: a new polycarboxylic acid graft copolymer material, which is made of the following components in percentage by mass and can form a self-assembled nanocarbon film on a metal surface:

[0007] Polyacrylic acid, molecular weight 4000-7000, accounting for 20-30%;

[0008] Polymaleic acid, molecular weight 2000-4500, accounting for 10-20%;

[0009] Octadecanyl propanolamine, purity 97-99%, accounting for 15-25%;

[0010] Surfactant selected from tallow amine, hexadecylamine and octadecylamine, accounting for 5-15%, wherein the amino content is 25-35%;

[0011] Bifunctional catalysts, accounting for 0.8-1.2%;

[0012] A modified azole compound selected from benzotriazole and methylbenzotriazole, accounting for 0.8-1.5%;

[0013] Water accounts for 50-70%.

[0014] Preferably, the bifunctional catalyst is a metal organic framework material, comprising:

[0015] The catalyst is used to promote both polymerization and cross-linking reactions;

[0016] The particle size of the catalyst ranges from 10 to 50 nanometers;

[0017] The catalyst contains copper and zinc transition metal ions to improve the material's corrosion resistance.

[0018] Preferably, the surfactant is composed of the following components by mass percentage:

[0019] Tallow amine, accounting for 30-50% of the total surfactant;

[0020] Hexadecylamine, accounting for 20-40% of the total surfactant;

[0021] Octadecanamine accounts for 10-30% of the total surfactant.

[0022] Preferably, the modified azole compound is prepared by the following steps:

[0023] Mix benzotriazole and methylbenzotriazole in a ratio of 1:1 to 3:1;

[0024] Add ethanolamine to the mixture to perform solvation treatment, control the temperature at 60-80° C., and continue for 1-3 hours;

[0025] The obtained product is cooled to room temperature to obtain a modified azole compound.

[0026] Preferably, the mixing method of polyacrylic acid and polymaleic acid includes:

[0027] The polyacrylic acid is stirred at a speed of 300 to 600 rpm;

[0028] While stirring, slowly add polymaleic acid and raise the temperature to 100-130°C;

[0029] Maintain this temperature and continue stirring for 1 to 2 hours to allow the two polymer acids to be fully mixed.

[0030] Preferably, a chain extender is added during the preparation process, and the preparation steps include:

[0031] At the end of the grafting reaction, low molecular weight polyvinyl alcohol is gradually added by controlling the dropping speed at 1 to 5 ml / min;

[0032] Stir evenly and keep the system temperature at 80-100°C;

[0033] The reaction is continued for 2 to 4 hours to ensure that the chain extender is evenly distributed in the polymer network and to adjust the molecular weight and chain spacing of the final polymer.

[0034] Preferably, the material is processed by the following steps when forming the self-assembled nanocarbon film:

[0035] The prepared polycarboxylic acid graft copolymer is pretreated under acidic conditions, and the pH value is controlled at 2.5 to 4.5;

[0036] Self-assembly was carried out under alkaline conditions, with the pH value controlled at 8.5-10.5;

[0037] During the self-assembly process, a trace amount of zinc ions is added at a concentration of 1 to 5 mM to stabilize the membrane layer.

[0038] Preferably, the stabilization treatment of the nanocarbonized film comprises the following steps:

[0039] Keep the film in a moist environment at room temperature for 24 to 48 hours;

[0040] Gradually reduce the humidity to dry the film layer. The drying process lasts for 3 to 6 hours.

[0041] The final drying process is carried out at 50-80°C for 1-2 hours.

[0042] Preferably, the chain extender is low molecular weight polyvinyl alcohol with a molecular weight of 1000-2000, and its usage is 0.5-1.0% of the total mass of the polymer.

[0043] The present invention also provides a method for preparing a new polycarboxylic acid graft copolymer material, comprising the following steps:

[0044] Mix polyacrylic acid and polymaleic acid in proportion, heat to 100-130° C., and stir to form a uniform mixture;

[0045] Add octadecyl propanolamine, continue heating to 135-155°C, and keep stirring for 4-6 hours to carry out grafting reaction;

[0046] Add a bifunctional catalyst to the reaction system, and gradually add a surfactant and a modified azole compound, and continue the reaction while maintaining the temperature at 135-155°C;

[0047] Introduce a chain extender and control the dripping speed. Continue the reaction for 2 to 4 hours after the dripping.

[0048] The pH value of the reaction system is controlled at 8.5-10.5, and a trace amount of metal ions is added to form and stabilize the self-assembled nanocarbon film.

[0049] The present invention provides a new polycarboxylic acid graft copolymer material and a preparation method thereof. It has the following beneficial effects:

[0050] 1. The polycarboxylic acid graft copolymer new material of the present invention significantly enhances the anti-corrosion ability of the coating by forming a dense self-assembled nanocarbon film. In high salt spray and corrosive environments, the material exhibits extremely high durability, can effectively protect the metal substrate from corrosion, extend the service life of the equipment, and reduce maintenance requirements.

[0051] 2. The material of the present invention exhibits excellent anti-scaling performance and thermal stability in high-hardness water and high-temperature environments. The material can remain clean and efficient in a long-term circulating water system, while maintaining its physical and chemical stability under high-temperature conditions, ensuring continuous and efficient operation of the equipment.

[0052] 3. The material of the present invention has excellent mechanical strength and toughness, and can maintain excellent adhesion and structural integrity over a wide temperature range. The material is suitable for a variety of extreme environments, including low and high temperature scenarios, ensuring that the coating provides reliable protection in different applications, with strong adaptability and a wide range of applications. DETAILED DESCRIPTION

[0053] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0054] The embodiment of the present invention provides a new polycarboxylic acid graft copolymer material, which is made of the following components in percentage by mass and can form a self-assembled nanocarbon film on a metal surface:

[0055] Polyacrylic acid, molecular weight 4000-7000, accounting for 20-30%;

[0056] Polymaleic acid, molecular weight 2000-4500, accounting for 10-20%;

[0057] Octadecanyl propanolamine, purity 97-99%, accounting for 15-25%;

[0058] The surfactant is selected from tallow amine, hexadecylamine and octadecylamine, accounting for 5-15%, of which the amino content is 25-35%. First, the carboxyl groups of polyacrylic acid and polymaleic acid can chemically adsorb with the metal surface to form a preliminary bonding layer. Subsequently, octadecyl propanolamine and surfactants further cover the metal surface through their hydrophobic long-chain structures to form a hydrophobic protective layer. This layer structure can significantly reduce the penetration of corrosive substances, thereby improving the protective effect of metals. Through the action of octadecyl propanolamine and surfactants, the scaling tendency of the metal surface is reduced, and the service life of the equipment is extended;

[0059] Bifunctional catalysts, accounting for 0.8-1.2%;

[0060] The modified azole compound is selected from benzotriazole and methylbenzotriazole, accounting for 0.8-1.5%. The bifunctional catalyst accelerates the reaction and promotes the stability of the film layer in this process. By catalyzing the cross-linking reaction, the film layer is formed more quickly and evenly. The modified azole compound further enhances the adhesion and corrosion resistance of the film layer through the coordination reaction with the metal ions. The bifunctional catalyst enables the material to form a dense film layer under low temperature conditions, increasing the application range of the material;

[0061] Water, accounting for 50-70%, can fully mix and contact various components during the reaction process, thereby forming a uniform polycarboxylic acid graft copolymer.

[0062] In a preferred embodiment of the present invention, the bifunctional catalyst is a metal organic framework material, comprising:

[0063] The catalyst is used to promote polymerization and cross-linking reactions at the same time. In the present invention, the metal organic framework material is designed to have dual functions: on the one hand, it promotes the polymerization reaction between polyacrylic acid, polymaleic acid and octadecyl propanolamine, so that the material can form a film quickly; on the other hand, the metal organic framework material can also promote the cross-linking reaction inside the material, enhancing the strength and stability of the polymer network. This dual catalytic effect effectively improves the film-forming speed of the material and the density of the film layer, ensuring that the material forms a uniform and firm protective film on the metal surface, thereby improving the film-forming speed of the material. At the same time, the density and stability of the film layer are also effectively enhanced, thereby greatly improving the corrosion resistance and mechanical strength of the material.

[0064] The particle size of the catalyst ranges from 10 to 50 nanometers. Nano-scale catalyst particles have a larger specific surface area and can provide more active sites, which is extremely important for promoting chemical reactions. The smaller particle size allows the catalyst to be more evenly dispersed in the polymer matrix, ensuring the uniformity of the reaction. By controlling the particle size of the catalyst within the range of 10 to 50 nanometers, the efficient dispersion and reaction activity of the catalyst are ensured, so that the material has a uniform microstructure and excellent physical properties, especially improving the density and mechanical strength of the film layer;

[0065] The catalyst contains copper and zinc transition metal ions to improve the corrosion resistance of the material. Zinc ions can form strong bonds with the carboxyl groups in polyacrylic acid and polymaleic acid, which not only significantly enhances the corrosion resistance of the material, but also improves the adhesion and self-healing ability of the film layer, thereby greatly improving the comprehensive protection effect and service life of the material.

[0066] In a preferred embodiment of the present invention, the surfactant is composed of the following components by mass percentage:

[0067] Tallow amine, which accounts for 30-50% of the total surfactant, is a long-chain fatty amine with high hydrophobicity. Its long-chain alkyl group can effectively cover the metal surface to form a hydrophobic barrier, preventing water molecules and other corrosive media from directly contacting the metal surface. In addition, the amine group in tallow amine can form hydrogen bonds or ion pairs with the carboxyl groups in polyacrylic acid and polymaleic acid, thereby enhancing the stability of the film layer. The introduced tallow amine improves the hydrophobicity and water resistance of the material, significantly enhances the anti-corrosion effect of the film layer, and further enhances the stability and mechanical strength of the film layer through the formation of hydrogen bonds or ion pairs;

[0068] Hexadecylamine accounts for 20-40% of the total surfactant. Hexadecylamine has good dispersibility and wettability. It acts as a lubricant in the material system, allowing the polycarboxylic acid graft copolymer to be evenly distributed on the metal surface during the film-forming process to form a dense and uniform film layer. At the same time, the moderate chain length of hexadecylamine enables it to provide sufficient hydrophobicity and synergize with other ingredients to avoid excessive rigidity of the film layer. By using hexadecylamine, the uniformity and density of the film layer can be effectively improved, ensuring that the material forms a uniform protective film on the metal surface, thereby enhancing the overall protective effect and maintaining the appropriate flexibility of the film layer;

[0069] Octadecanamine accounts for 10-30% of the total surfactant. The long chain structure of octadecylamine makes it more hydrophobic and chemically stable. Octadecanamine can further enhance the water resistance and corrosion resistance of the film. In addition, octadecylamine can play its role at a lower concentration, forming a tight molecular arrangement, thereby reducing the permeability of the film and improving the physical barrier effect of the film. The use of octadecylamine effectively enhances the hydrophobicity and chemical stability of the film, making the material have a longer service life in a corrosive environment, while reducing the amount of materials used and reducing production costs.

[0070] Through the ratio of tallow amine, hexadecylamine and octadecylamine, the surfactant system of the present invention significantly improves the comprehensive performance of the film layer, including uniformity, density, hydrophobicity and durability, so that the material exhibits excellent protective performance and long-term stability in various complex environments.

[0071] In a preferred embodiment of the present invention, the modified azole compound is prepared by the following steps:

[0072] Mix benzotriazole and methylbenzotriazole in a ratio of 1:1 to 3:1. Both benzotriazole and methylbenzotriazole are commonly used anticorrosive agents. Their molecular structures contain active nitrogen atoms and aromatic rings. These characteristics enable them to form stable chelates with metal ions to prevent metal corrosion. A higher proportion of benzotriazole can enhance the material's antioxidant properties, while a higher proportion of methylbenzotriazole can improve the material's durability and chemical stability. This mixing step ensures the performance balance of the modified azole compounds in different application environments. By adjusting the ratio of benzotriazole to methylbenzotriazole, the modified azole compounds achieve the best balance between anticorrosion performance and chemical stability, ensuring the long-term stability of the material in complex environments.

[0073] Add ethanolamine to the mixture and perform solvation treatment. The temperature is controlled at 60-80°C for 1-3 hours. Ethanolamine is a commonly used organic solvent with good polarity and solubility. It can effectively dissolve and evenly disperse benzotriazole and methylbenzotriazole. The temperature of the solvation treatment is controlled at 60-80°C and the duration is 1-3 hours. The purpose of this process is to fully disperse benzotriazole and methylbenzotriazole in the solvent and form a stable complex with ethanolamine. The introduction of ethanolamine not only enhances the solubility of azole compounds, but also further enhances the anti-corrosion properties of modified azole compounds through the interaction of its hydroxyl and amine groups with benzotriazole and methylbenzotriazole, thereby ensuring the uniform dispersion and dissolution of benzotriazole and methylbenzotriazole, enhancing the chemical stability and anti-corrosion properties of the modified azole compounds, and making the material perform well in high humidity and highly corrosive environments;

[0074] The obtained product is cooled to room temperature to obtain a modified azole compound. During the cooling process, the complex of benzotriazole and methylbenzotriazole with ethanolamine gradually precipitates to form a stable modified azole compound, which not only improves the purity of the modified azole compound, but also reduces the occurrence of side reactions, thereby ensuring the high-efficiency anti-corrosion performance of the product.

[0075] In a preferred embodiment of the present invention, the mixing method of polyacrylic acid and polymaleic acid comprises:

[0076] Stirring polyacrylic acid at a speed of 300 to 600 rpm. During the stirring process, the polyacrylic acid molecular chains are stretched and unfolded, increasing their contact area with the surrounding environment. This operation helps to reduce the viscosity of polyacrylic acid, making it easier to mix with the subsequently added polymaleic acid. In addition, stirring can also promote the dissolution of tiny aggregates in polyacrylic acid, further improving its uniformity in the solution. By initially stirring polyacrylic acid at a speed of 300 to 600 rpm, the dispersibility and solubility of polyacrylic acid can be effectively improved, ensuring the uniform mixing of the various components in the subsequent reaction, thereby improving the performance stability and uniformity of the final material;

[0077] While stirring, slowly add polymaleic acid and raise the temperature to 100-130°C. The heating process helps reduce the viscosity of polymaleic acid, making it easier to mix with polyacrylic acid. In addition, heating can also stimulate the movement of polymer chains, increase the mutual diffusion rate of the two polymer molecules, and thus accelerate their mixing. By slowly adding polymaleic acid and raising the temperature to 100-130°C, the uniform mixing of the two polymer acids can be effectively promoted, and the structural integrity of the polymer network can be enhanced, thereby improving the mechanical properties and durability of the material;

[0078] Maintaining this temperature, continue stirring for 1 to 2 hours to fully mix the two polymer acids. By continuing stirring for 1 to 2 hours, the polyacrylic acid and polymaleic acid are fully mixed to form a uniform polymer matrix, which lays a solid foundation for the subsequent polymerization and film-forming process, thereby improving the comprehensive performance of the material, especially the uniformity and density of the film layer.

[0079] In a preferred embodiment of the present invention, a chain extender is added during the preparation process, and the preparation steps include:

[0080] At the end of the grafting reaction, the low molecular weight polyvinyl alcohol is gradually added by controlling the dripping speed, and the dripping speed is controlled at 1 to 5 ml / min. At the end of the preparation, the low molecular weight polyvinyl alcohol is slowly dripped into the reaction system, and the dripping speed is controlled at 1 to 5 ml / min. By controlling the dripping speed, it is possible to ensure that the chain extender and the polycarboxylic acid graft copolymer react fully, and avoid the situation where the local reaction is incomplete or the product is uneven due to too fast addition. The introduction of low molecular weight polyvinyl alcohol can effectively extend the length of the polymer chain and enhance the strength and elasticity of the polymer network, thereby improving the mechanical properties and chemical stability of the material. At the same time, by controlling the dripping speed, the uniformity of the reaction and the consistency of the product quality are ensured;

[0081] Stir evenly and keep the system temperature at 80-100°C. Even stirring can ensure that polyvinyl alcohol is fully diffused in the entire reaction system, thereby avoiding uneven local reactions or incomplete chain structures. At the same time, even stirring can also prevent polymers from agglomerating or forming uneven chain spacing during the reaction process, ensuring the homogeneity of the material. By fully stirring at this temperature, the chain extender can be evenly distributed in the polymer network, effectively improving the structural uniformity and mechanical properties of the material, and ensuring the high quality of the final product.

[0082] Continue the reaction for 2 to 4 hours to ensure that the chain extender is evenly distributed in the polymer network and adjust the molecular weight and chain spacing of the final polymer. By continuing the reaction for 2 to 4 hours to ensure sufficient reaction between the chain extender and the polymer, not only the molecular weight and mechanical properties of the material can be improved, but also the chain spacing can be optimized, thereby significantly enhancing the comprehensive performance of the material, especially achieving a balance between high strength and high toughness.

[0083] In a preferred embodiment of the present invention, the material is processed by the following steps when forming the self-assembled nanocarbon film:

[0084] The prepared polycarboxylic acid graft copolymer is pretreated under acidic conditions with a pH value of 2.5 to 4.5. The purpose of this step is to activate the active sites in the polymer and remove possible surface impurities or oxide layers, thereby creating a clean and reactive surface for the subsequent self-assembly process. The acidic environment can partially protonate the carboxyl and amine groups in the polymer and enhance their chemical adsorption capacity with the metal surface. At the same time, this acidic environment can effectively remove oxides and other impurities on the metal surface, ensuring the compactness and uniformity of the film layer during the self-assembly process, thereby providing an ideal chemical environment for the subsequent self-assembly process and significantly improving the adhesion and uniformity of the film layer.

[0085] Self-assembly is carried out under alkaline conditions, and the pH value is controlled at 8.5-10.5. In an alkaline environment, the polarity of the polymer chain is enhanced, so that it can be arranged more closely together to form a stable nanocarbon film. The film layer has high strength and high density, which can effectively prevent the penetration of corrosive ions and oxygen, and provide long-term anti-corrosion protection. Self-assembly under alkaline conditions can promote the polymer chain to form a stable nanocarbon film on the metal surface, significantly enhancing the density and protective performance of the film layer, thereby providing long-lasting protection for the metal substrate;

[0086] During the self-assembly process, a trace amount of zinc ions is added at a concentration of 1 to 5 mM to stabilize the film. The introduction of zinc ions can also form a protective zinc oxide film on the metal surface. This film has excellent corrosion resistance and can prevent further erosion by oxygen and moisture. This layer of zinc oxide film works together with the nanocarbon film to greatly improve the overall protective effect of the film. By adding zinc ions and stabilizing the film, not only the chemical stability of the nanocarbon film is enhanced, but also the durability and corrosion resistance of the film are further improved by forming an additional protective oxide film, thereby providing double protection for the metal substrate.

[0087] In a preferred embodiment of the present invention, the stabilization treatment of the nanocarbonized film comprises the following steps:

[0088] At room temperature, keep the film in a humid environment for 24 to 48 hours. The humid environment can be maintained by placing potassium sulfate or sodium chloride in a closed container. These salt solutions can provide stable humidity conditions. In this process, the molecules inside the film are rearranged to form a tighter structure. Water molecules act as a lubricant in this process, making the interaction between molecules more uniform, thereby ensuring the uniformity and structural stability of the nanocarbonized film, preventing stress concentration and cracking of the film during the drying process, and laying a good foundation for subsequent drying treatment;

[0089] Gradually reduce the humidity to dry the film layer. The drying process lasts for 3 to 6 hours. The gradual reduction of humidity can be achieved by gradually replacing the humidity control solution or by precisely controlling the humidity adjustment equipment. During this process, the water molecules in the film layer slowly move out, while the internal polymer chains move closer to each other and lock their positions. This slow drying process ensures the synchronous shrinkage of the inside and outside of the film layer, and prevents the accumulation of internal stress caused by uneven drying. By gradually reducing the humidity and slowly drying the film layer, it can effectively prevent uneven stress on the surface and inside of the film layer, ensure that the dried film layer maintains uniform thickness and good structural integrity, and further enhance the mechanical properties of the film layer.

[0090] The final drying treatment is carried out at 50-80°C for 1-2 hours. During the drying process, the drying treatment can enhance the thermal motion of the polymer chain, thereby further filling the tiny pores in the film layer and forming a denser structure. In addition, the drying temperature is controlled between 50 and 80°C to prevent polymer degradation caused by excessive temperature and ensure the structural stability of the film layer. The drying time is controlled at 1-2 hours, which is sufficient to complete the thorough drying of the film layer and make the film layer have excellent physical and chemical properties. The final drying treatment ensures the density and mechanical strength of the nanocarbonized film, completely removes the residual moisture in the film layer, and enables the film layer to maintain excellent protective properties and long-term stability under high temperature and high humidity environments.

[0091] In a preferred embodiment of the present invention, the chain extender is a low molecular weight polyvinyl alcohol with a molecular weight of 1000-2000, and its dosage is 0.5-1.0% of the total mass of the polymer. The purpose of selecting low molecular weight polyvinyl alcohol is to extend the length of the polymer chain and improve the strength and toughness of the material without significantly increasing the viscosity of the material. The molecular weight range of 1000-2000 ensures that the polyvinyl alcohol can be fully dissolved in the system and can undergo esterification reaction with the carboxyl group in the polymer through its hydroxyl group, thereby increasing the molecular weight and chain length of the polymer, and increasing the mechanical strength and durability of the material, while maintaining good solubility and processing properties, so that the material performs well in complex environments.

[0092] The present invention also provides a method for preparing a new polycarboxylic acid graft copolymer material, comprising the following steps:

[0093] Mix polyacrylic acid and polymaleic acid in proportion, heat to 100-130° C., and stir to form a uniform mixture;

[0094] Add octadecyl propanolamine, continue heating to 135-155°C, and keep stirring for 4-6 hours to carry out grafting reaction;

[0095] Add a bifunctional catalyst to the reaction system, and gradually add a surfactant and a modified azole compound, and continue the reaction while maintaining the temperature at 135-155°C;

[0096] Introduce a chain extender and control the dripping speed. Continue the reaction for 2 to 4 hours after the dripping.

[0097] The pH value of the reaction system is controlled at 8.5-10.5, and a trace amount of metal ions is added to form and stabilize the self-assembled nanocarbon film.

[0098] In order to better understand the present invention, the above contents are described in detail below in conjunction with specific embodiments.

[0099] Example 1: High-strength corrosion-resistant material

[0100] Material formula:

[0101] Polyacrylic acid: 25%

[0102] Polymaleic acid: 15%

[0103] Octadecyl propanolamine: 20%

[0104] Surfactant: 10%

[0105] Tallowamine: 40%

[0106] Hexadecylamine: 30%

[0107] Octadecanamine: 30%

[0108] Bifunctional catalyst: 1.0%

[0109] Modified azole compounds: 1.2%

[0110] Low molecular weight polyvinyl alcohol: 0.8%

[0111] Water: 56%

[0112] Preparation process:

[0113] The polyacrylic acid was stirred in a stirrer at a speed of 400 rpm, while the polymaleic acid was slowly added and the temperature was raised to 110°C.

[0114] The stirring was maintained for 1.5 hours to allow the two polymers to be thoroughly mixed.

[0115] At the end of the grafting reaction, low molecular weight polyvinyl alcohol was gradually added at a rate of 3 ml per minute by controlling the dropwise addition rate.

[0116] The reaction was continued with stirring and the temperature was maintained at 90 °C for 3 hours to ensure that the chain extender was evenly distributed in the polymer network.

[0117] After the reaction was completed, the membrane was pretreated at pH 3.0 for 1 hour under acidic conditions, and then self-assembled at pH 9.0 under alkaline conditions, during which 3 mM zinc ions were added to stabilize the membrane.

[0118] Example 2: High toughness anti-scaling material

[0119] Material formula:

[0120] Polyacrylic acid: 22%

[0121] Polymaleic acid: 18%

[0122] Octadecyl propanolamine: 22%

[0123] Surfactant: 12%

[0124] Tallowamine: 50%

[0125] Hexadecylamine: 20%

[0126] Octadecanamine: 30%

[0127] Bifunctional catalyst: 0.8%

[0128] Modified azole compounds: 1.0%

[0129] Low molecular weight polyvinyl alcohol: 0.5%

[0130] Water: 54%

[0131] Preparation process:

[0132] The polyacrylic acid was stirred at a speed of 500 rpm while the polymaleic acid was slowly added and the temperature was raised to 120°C.

[0133] The mixture was stirred for 2 hours to allow the two polymer acids to be fully mixed.

[0134] At the end of the grafting reaction, low molecular weight polyvinyl alcohol was gradually added at a rate of 4 ml per minute.

[0135] The reaction was continued with stirring and the temperature was maintained at 95 °C for 4 hours to ensure that the chain extender was evenly distributed in the polymer network.

[0136] After pretreatment at pH 2.5 for 1.5 hours under acidic conditions, self-assembly was carried out under alkaline conditions at pH 8.5, during which 5 mM zinc ions were added for membrane stabilization.

[0137] Example 3: Anticorrosion materials for low temperature applications

[0138] Material formula:

[0139] Polyacrylic acid: 28%

[0140] Polymaleic acid: 12%

[0141] Octadecyl propanolamine: 18%

[0142] Surfactant: 8%

[0143] Tallowamine: 30%

[0144] Hexadecylamine: 40%

[0145] Octadecanamine: 30%

[0146] Bifunctional catalyst: 1.2%

[0147] Modified azole compounds: 1.5%

[0148] Low molecular weight polyvinyl alcohol: 1.0%

[0149] Water: 56%

[0150] Preparation process:

[0151] The polyacrylic acid was stirred at a speed of 350 rpm while the polymaleic acid was slowly added and the temperature was raised to 100°C.

[0152] The mixture was stirred for 1 hour to allow the two polymer acids to be fully mixed.

[0153] At the end of the grafting reaction, low molecular weight polyvinyl alcohol was gradually added at a rate of 2 ml per minute.

[0154] The reaction was continued with stirring and the temperature was maintained at 80 °C for 2 h to ensure that the chain extender was evenly distributed in the polymer network.

[0155] After pretreatment at pH 4.5 for 1 hour under acidic conditions, self-assembly was carried out under alkaline conditions at pH 10.5, during which 1 mM zinc ions were added for membrane stabilization.

[0156] Comparative experiment 1: Anti-corrosion performance test

[0157] Experimental purpose: To evaluate the anti-corrosion performance of the polycarboxylic acid graft copolymer new material of the present invention in a salt spray environment and compare it with common anti-corrosion coating materials.

[0158] Experimental Materials:

[0159] Experimental group: carbon steel samples coated with the novel polycarboxylic acid graft copolymer material of the present invention.

[0160] Control group A: Carbon steel sample coated with traditional epoxy resin anti-corrosion coating.

[0161] Control group B: Carbon steel sample coated with polyurethane coating.

[0162] Control group C: Carbon steel sample coated with inorganic zinc coating.

[0163] Experimental conditions:

[0164] Salt spray test chamber: 3.5% NaCl solution

[0165] Temperature: 35℃

[0166] Test time: 500 hours, 1000 hours and 1500 hours

[0167] Sample size: 50mmx50mmx2mm

[0168] Evaluation indicators:

[0169] Coating damage area

[0170] Metal Weightlessness

[0171] Corrosion area percentage

[0172] Experimental procedures

[0173] Sample preparation:

[0174] Use carbon steel substrate of the same size;

[0175] The material of the present invention and the materials of the control group were coated respectively, and the coating thickness was controlled at 50 microns;

[0176] Allow the coating to cure at room temperature for 24 hours.

[0177] Salt spray test:

[0178] All samples were placed in a salt spray test chamber and exposed to a 3.5% NaCl salt spray environment with the temperature controlled at 35°C;

[0179] The exposure times were set to 500 hours, 1000 hours, and 1500 hours respectively.

[0180] Sample observation:

[0181] Samples were taken out after each exposure time point and examined for coating damage using a microscope;

[0182] The coating damage area was measured and the corrosion area on the metal surface was recorded.

[0183] Metal weight loss measurement:

[0184] Wash the samples with deionized water to remove attached salts;

[0185] The samples were dried in a drying oven and the weight loss of each sample was measured.

[0186] Data recording and analysis:

[0187] Record the coating damage area, metal weight loss and percentage of corrosion area;

[0188] The antiseptic properties of the material of the present invention and those of the control groups were compared.

[0189] The comparative experimental data are shown in Table 1:

[0190] Table 1 Anti-corrosion performance test results

[0191]

[0192]

[0193] From the data in Table 1, we can get:

[0194] As the exposure time increases, the coating damage area, metal weight loss and corrosion area percentage of each sample all show an increasing trend. However, the experimental group of the present invention shows significantly better anti-corrosion performance than the control groups under all test conditions, which shows that the polycarboxylic acid graft copolymer new material of the present invention has significant advantages in anti-corrosion performance, far exceeding traditional anti-corrosion coating materials.

[0195] Comparative experiment 2: Anti-scaling performance test

[0196] Experimental purpose: To evaluate the anti-fouling performance of the polycarboxylic acid graft copolymer novel material of the present invention and compare it with common anti-fouling coating materials.

[0197] Experimental Materials:

[0198] Experimental group: samples of the heat exchanger surface coated with the polycarboxylic acid graft copolymer novel material of the present invention.

[0199] Control group A: heat exchanger sample coated with traditional sodium polyacrylate anti-fouling coating.

[0200] Control Group B: Heat exchanger samples coated with phosphate treatment coating.

[0201] Control group C: heat exchanger samples without coating.

[0202] Experimental conditions:

[0203] Hard water hardness: 200~500ppm

[0204] Testing time: 4 weeks

[0205] Water temperature: 60℃

[0206] Circulation speed: 2L / min

[0207] Sample size: 50mmx50mmx2mm

[0208] Evaluation indicators:

[0209] Scaling amount

[0210] Heat exchange efficiency decrease percentage

[0211] Surface scaling thickness

[0212] Experimental procedures

[0213] Sample preparation:

[0214] Use the same size heat exchanger metal substrate.

[0215] The material of the present invention and the materials of the control groups were coated respectively, and the coating thickness was controlled at 50 microns.

[0216] The samples are cured and ready for testing.

[0217] Hard water cycle test:

[0218] Each group of samples was installed in a simulated heat exchange system;

[0219] Simulated hard water with a hardness of 200-500 ppm was circulated in the system at a rate of 2 L / min at 60°C for 4 weeks.

[0220] Sample observation:

[0221] The heat exchange surface of each sample was inspected once a week and the microstructure of the scale was observed using a microscope;

[0222] Measure and record the decrease in heat exchange efficiency.

[0223] Scaling amount determination:

[0224] After the test, each sample was removed and rinsed with deionized water to remove the scale particles floating on the surface;

[0225] After drying, the samples were weighed and the amount of scaling was calculated.

[0226] Scale thickness measurement:

[0227] The thickness of the scale was measured and recorded using an optical microscope or a scanning electron microscope.

[0228] Data recording and analysis:

[0229] Record the amount of scaling, percentage of heat exchange efficiency reduction and scaling thickness of each group;

[0230] The anti-scaling performance of the material of the present invention was compared with that of each control group.

[0231] The comparative experimental data are shown in Table 2:

[0232] Table 2 Anti-scaling performance test results

[0233]

[0234]

[0235] From the data in Table 2, we can get:

[0236] As the test time increases, the amount of scaling, the decrease in heat exchange efficiency and the thickness of surface scaling of each group of samples all increase. However, the experimental group of the present invention shows significantly better anti-scaling performance than the control groups under all test conditions. It can be concluded that the polycarboxylic acid graft copolymer new material of the present invention is superior to traditional materials in anti-scaling performance, significantly reduces scaling formation, and maintains efficient operation of the heat exchanger.

[0237] Comparative experiment 3: Mechanical strength and durability test

[0238] Experimental purpose: To evaluate the mechanical strength and durability of the polycarboxylic acid graft copolymer new material of the present invention under different temperature conditions, and to compare it with common coating materials.

[0239] Experimental Materials:

[0240] Experimental group: carbon steel samples coated with the novel polycarboxylic acid graft copolymer material of the present invention.

[0241] Control group A: Carbon steel sample coated with conventional epoxy coating.

[0242] Control group B: Carbon steel sample coated with polyurethane coating.

[0243] Control group C: Carbon steel sample coated with silane coating.

[0244] Experimental conditions:

[0245] Temperature conditions: -20℃, 25℃ and 150℃

[0246] Sample size: 50mmx50mmx2mm

[0247] Evaluation indicators: maximum tensile strength, impact toughness, coating adhesion, surface cracking and peeling

[0248] Experimental procedures

[0249] Sample preparation:

[0250] Use carbon steel substrates of the same size;

[0251] The material of the present invention and the materials of the control group were coated respectively, and the coating thickness was controlled at 50 microns;

[0252] After the samples were cured at room temperature for 24 hours, they were ready for testing.

[0253] Tensile strength test:

[0254] Each group of samples was pretreated in an environment of -20°C, 25°C, and 150°C for 2 hours;

[0255] The maximum tensile strength of each sample was tested using a tensile testing machine, and the maximum stress value when the sample broke was recorded.

[0256] Impact toughness test:

[0257] The impact test was carried out under the same temperature conditions, the impact toughness of the sample was measured using an impact testing machine, and the absorbed impact energy was recorded.

[0258] Coating Adhesion Test:

[0259] The standard adhesion test method is used to test the adhesion of the coating under different temperature conditions, and the force value or peeling area of ​​the coating is recorded.

[0260] Surface cracking and peeling observation:

[0261] The cracking and peeling of the sample surface were observed under a microscope, and the integrity of the coating was recorded and analyzed.

[0262] Data recording and analysis:

[0263] The maximum tensile strength, impact toughness, coating adhesion, surface cracking and peeling of each group were recorded;

[0264] The mechanical strength and durability of the material of the present invention were compared with those of the control groups.

[0265] The comparative experimental data are shown in Table 3:

[0266] Table 3 Mechanical strength and durability test results

[0267]

[0268]

[0269] From the data in Table 3, we can get:

[0270] The experimental group showed no obvious cracking or peeling at all temperatures, with the smallest peeling area, showing excellent durability. The control group C had the largest peeling area under high temperature conditions, reaching 8.3mm 2 , and the cracking phenomenon is obvious. Therefore, it can be concluded that the new polycarboxylic acid graft copolymer material of the present invention is significantly superior to traditional coating materials in terms of mechanical strength and durability, especially in different temperature conditions.

[0271] Comparative experiment 4: Heat resistance test

[0272] Experimental purpose: To evaluate the stability and heat resistance of the polycarboxylic acid graft copolymer new material of the present invention in a high temperature environment, and to compare it with common protective coating materials.

[0273] Experimental Materials:

[0274] Experimental group: carbon steel samples coated with the novel polycarboxylic acid graft copolymer material of the present invention.

[0275] Control group A: Carbon steel sample coated with conventional polyurethane coating.

[0276] Control group B: carbon steel sample coated with polytetrafluoroethylene.

[0277] Control group C: Carbon steel sample coated with epoxy resin coating.

[0278] Experimental conditions:

[0279] Temperature settings: 150°C, 200°C and 250°C

[0280] Exposure time: 48 hours

[0281] Sample size: 50mmx50mmx2mm

[0282] Evaluation indicators:

[0283] Thermal decomposition temperature of coating

[0284] Coating quality loss

[0285] Coating surface changes

[0286] Experimental procedures

[0287] Sample preparation:

[0288] Use carbon steel substrates of the same size;

[0289] The material of the present invention and the materials of the control group were coated respectively, and the coating thickness was controlled at 50 microns;

[0290] After the samples were cured at room temperature for 24 hours, they were ready for testing.

[0291] High temperature exposure test:

[0292] Each group of samples was placed in an environment of 150°C, 200°C and 250°C, respectively, and heated continuously for 48 hours.

[0293] Three groups of samples were set at each temperature point, and the samples were taken out for analysis after the exposure.

[0294] Thermogravimetric analysis:

[0295] The thermal decomposition temperature of each group of samples was determined using a thermogravimetric analyzer, and the mass loss of the samples during the gradual heating process was recorded.

[0296] Mass loss determination:

[0297] The mass of the samples before and after high temperature exposure was measured using a precision electronic balance, and the mass loss percentage was calculated.

[0298] Surface change observation:

[0299] The bubble formation, cracking and shedding on the sample surface were observed under a microscope, and the surface changes of the coating were recorded.

[0300] Data recording and analysis:

[0301] Record the thermal decomposition temperature, mass loss percentage, and surface changes of each group of samples;

[0302] The heat resistance of the material of the present invention was compared with that of each control group.

[0303] The comparative experimental data are shown in Table 4:

[0304] Table 4 Heat resistance test results

[0305]

[0306] From the data in Table 4, we can get:

[0307] As the temperature increases, the thermal decomposition temperature of the coating of each group of samples decreases, the mass loss increases, and the surface changes become more obvious. However, the experimental group of the present invention shows better heat resistance than the control group under all temperature conditions, which shows that the polycarboxylic acid graft copolymer new material of the present invention is significantly better than the traditional coating material in terms of heat resistance, especially in a high temperature environment. It can maintain high stability and low mass loss.

[0308] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A new polycarboxylic acid graft copolymer material, characterized in that: The material is made of the following components by mass percentage and can form a self-assembled nanocarbon film on the metal surface: Polyacrylic acid, molecular weight 4000-7000, accounting for 20-30%; Polymaleic acid, molecular weight 2000-4500, accounting for 10-20%; Octadecanyl propanolamine, purity 97-99%, accounting for 15-25%; Surfactant selected from tallow amine, hexadecylamine and octadecylamine, accounting for 5-15%, wherein the amino content is 25-35%; Bifunctional catalysts, accounting for 0.8-1.2%; A modified azole compound selected from benzotriazole and methylbenzotriazole, accounting for 0.8-1.5%; Water, accounting for 50-70%.

2. A new polycarboxylic acid graft copolymer material according to claim 1, characterized in that: The bifunctional catalyst is a metal organic framework material, comprising: The catalyst is used to promote both polymerization and cross-linking reactions; The particle size of the catalyst ranges from 10 to 50 nanometers; The catalyst contains copper and zinc transition metal ions to improve the material's corrosion resistance.

3. A new polycarboxylic acid graft copolymer material according to claim 1, characterized in that: The surfactant is composed of the following components by mass percentage: Tallow amine, accounting for 30-50% of the total surfactant; Hexadecylamine, accounting for 20-40% of the total surfactant; Octadecanamine accounts for 10-30% of the total surfactant.

4. The new polycarboxylic acid graft copolymer material according to claim 1, characterized in that: The modified azole compound is prepared by the following steps: Mix benzotriazole and methylbenzotriazole in a ratio of 1:1 to 3:1; Add ethanolamine to the mixture to perform solvation treatment, control the temperature at 60-80° C., and continue for 1-3 hours; The obtained product is cooled to room temperature to obtain a modified azole compound.

5. The new polycarboxylic acid graft copolymer material according to claim 1, characterized in that: Mixing methods of polyacrylic acid and polymaleic acid include: The polyacrylic acid is stirred at a speed of 300 to 600 rpm; While stirring, slowly add polymaleic acid and raise the temperature to 100-130°C; Maintain this temperature and continue stirring for 1 to 2 hours to allow the two polymer acids to be fully mixed.

6. The new polycarboxylic acid graft copolymer material according to claim 1, characterized in that: A chain extender is added during the preparation process, and the preparation steps include: At the end of the grafting reaction, low molecular weight polyvinyl alcohol is gradually added by controlling the dropping speed at 1 to 5 ml / min; Stir evenly and keep the system temperature at 80-100°C; The reaction is continued for 2 to 4 hours to ensure that the chain extender is evenly distributed in the polymer network and to adjust the molecular weight and chain spacing of the final polymer.

7. The new polycarboxylic acid graft copolymer material according to claim 1, characterized in that: The material is processed by the following steps when forming a self-assembled nanocarbon film: The prepared polycarboxylic acid graft copolymer is pretreated under acidic conditions, and the pH value is controlled at 2.5 to 4.5; Self-assembly was carried out under alkaline conditions, with the pH value controlled at 8.5-10.5; During the self-assembly process, a trace amount of zinc ions is added at a concentration of 1 to 5 mM to stabilize the membrane layer.

8. The new polycarboxylic acid graft copolymer material according to claim 1, characterized in that: The stabilization treatment of the nanocarbon film includes the following steps: Keep the film in a moist environment at room temperature for 24 to 48 hours; Gradually reduce the humidity to dry the film layer. The drying process lasts for 3 to 6 hours. The final drying process is carried out at 50-80°C for 1-2 hours.

9. The new polycarboxylic acid graft copolymer material according to claim 6, characterized in that: The chain extender is low molecular weight polyvinyl alcohol with a molecular weight of 1000-2000, and its usage is 0.5-1.0% of the total weight of the polymer.

10. A method for preparing a new polycarboxylic acid graft copolymer material, characterized in that: A new polycarboxylic acid graft copolymer material according to any one of claims 1 to 9, comprising the following steps: Mix polyacrylic acid and polymaleic acid in proportion, heat to 100-130° C., and stir to form a uniform mixture; Add octadecyl propanolamine, continue heating to 135-155°C, and keep stirring for 4-6 hours to carry out grafting reaction; Add a bifunctional catalyst to the reaction system, and gradually add a surfactant and a modified azole compound, and continue the reaction while maintaining the temperature at 135-155°C; Introduce a chain extender and control the dripping speed. Continue the reaction for 2 to 4 hours after the dripping. The pH value of the reaction system is controlled at 8.5-10.5, and a trace amount of metal ions is added to form and stabilize the self-assembled nano carbonized film.